Response Adaptive Randomization Using Biomarkers with Exponentially Decreasing Probability Sequence - Palanisamy, T.; Ravichandran, J.; Ramesh, Midhuna (International Journal of Statistics in Medical Research, 2025)
In this article, it is proposed to study the application of Response Adaptive Randomization (RAR) design in clinical trials. The approach involves the prediction of treatment outcomes based on the biomarker of patients using a regression model. The focus is on rare diseases to efficiently allot the patients among various treatments so as to ensure not only the clinical rights but also the maximum possible benefits to the patients even when they are in clinical trials. Initially, the method uses conventional equal randomization to understand how well every treatment works in patients and this initial duration is known as burn-in period. The proposed work allocates patients to treatments by using an exponentially decreasing probability sequence instead of the existing linearly decreasing sequence to have higher allocation probability to the efficient treatment. In the case of rare disease, it is observed from simulation study that the use of exponentially decreasing probability sequence in RAR design increases the benefit to the patients in the clinical trials when compared to the existing method that uses linearly decreasing sequence. The study also investigates the performance of the proposed RAR design when used with different regression methods under various scenarios. The performance of the proposed design is measured by the proportion of patients assigned to the best treatment in addition to Type I error and power. From the impressive results, it is suggested that the proposed RAR design can be implemented practically in clinical trials of rare diseases without any apprehension.